Development of ethnoscience module on pond ecosystem, in Serawai Tribe, Seluma Regency - Kusumah, R G T; Andaria, M; Misriani, A; Purdiyanto; Samsilayurni (Journal of physics. Conference series, 2022)
This study aims to develop an ethnoscience module as a teaching material for pond ecosystems in science learning at Public Elementary School 36 Seluma Regency. The Research and Development (R & D) method is used in this study. The stages are potential and problem, data collection, product design, design validation, design revision, trial, product revision, usage trial, product revision, mass production. The information came from the village of Tanah Abang, the Serawai tribe and Public Elementary School 36 Seluma. The results showed that the final product in the form of an ethnoscience-based science module with an Artificial Ecosystem in the pond was suitable for use. This feasibility refers to the National Education Standards Agency (BSNP) in the category of having passed stage I and stage II by obtaining an average design feasibility score of 87%, material feasibility 86%, and presentation feasibility 83%. Thus obtained an average feasibility of 85%.